2002
DOI: 10.1046/j.1365-2273.2002.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective double-blind randomized controlled trial comparing the suitability of KTP laser tonsillectomy with conventional dissection tonsillectomy for day case surgery

Abstract: Tonsillectomy using a KTP laser has been performed increasingly but is not a routinely practised technique in the UK. In the USA, tonsillectomy is often performed as a day case procedure but, here in the UK, it is still standard practice to admit patients for overnight stay. We present the largest prospective double-blind randomized controlled trial to date (151 patients) comparing KTP laser with standard dissection tonsillectomy and assess the suitability of both procedures for day case surgery. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
(17 reference statements)
3
16
1
Order By: Relevance
“…PTH may have been reported as primary (generally defined as occurring within 24 hours of surgery), secondary (generally defined as occurring more than 24 hours postoperatively), or at an undefined or unspecified time. 8–108 Seventy-three studies contributed data to the meta-analysis (66 RCTs, 19,20,23,25,27,29,33,34,36,3841,43,44,46,47,49,50,5259,6264,67,71,72,7479,8184,88–92,95,101–105,108–122 6 nonrandomized trials, 24,35,37,45,48,94 and 1 prospective cohort study 70 ). The resulting subset of studies included the following tonsillectomy techniques: cold dissection, electrocautery, coblation, harmonic scalpel, laser, molecular resonance, thermal welding, and microdebrider.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTH may have been reported as primary (generally defined as occurring within 24 hours of surgery), secondary (generally defined as occurring more than 24 hours postoperatively), or at an undefined or unspecified time. 8–108 Seventy-three studies contributed data to the meta-analysis (66 RCTs, 19,20,23,25,27,29,33,34,36,3841,43,44,46,47,49,50,5259,6264,67,71,72,7479,8184,88–92,95,101–105,108–122 6 nonrandomized trials, 24,35,37,45,48,94 and 1 prospective cohort study 70 ). The resulting subset of studies included the following tonsillectomy techniques: cold dissection, electrocautery, coblation, harmonic scalpel, laser, molecular resonance, thermal welding, and microdebrider.…”
Section: Resultsmentioning
confidence: 99%
“…PTH may have been reported as primary (generally defined as occurring within 24 hours of surgery), secondary (generally defined as occurring >24 hours postoperatively), or at an undefined or unspecified time. 8…”
Section: Resultsmentioning
confidence: 99%
“…Few good randomized studies ( table 3 ) have compared laser tonsillectomies to other techniques [33][34][35][36] and although the PTB rates are not significantly different, they tend to be higher than the comparison group. Overall, there are few good reasons to select lasers as a tonsillectomy technique and disadvantages include cost, increased pain, and a prolonged healing phase.…”
Section: Surgical Technique: Other Methodsmentioning
confidence: 99%
“…Compared with standard dissection, the Harmonic scalpel method appears to be associated with less pain after surgery; compared with electrocautery, it seems to provide a reduction in pain throughout the postoperative recovery period [18]. In one of the largest prospective double-blind randomized controlled trial to date (151 patients) comparing KTP laser with standard dissection tonsillectomy, by Kothari et al [19], they found that there was significantly less peroperative haemorrhage if tonsillectomy was performed using the KTP laser, but it did caused more postoperative pain, more depression in mood and a higher rate of both reactionary and secondary haemorrhage, which was not significant when compared with conventional dissection and conclude that KTP laser tonsillectomy offers no benefit apart from less intraoperative bleeding over standard dissection tonsillectomy. In another study, Jackel et al [20], state that CO 2 LASER microsurgery improves the precision of tonsillectomy and provides a maximum protection for the peritonsillar tissue; the incidence of severe bleeding events being markedly reduced.…”
Section: Antibiotic Therapymentioning
confidence: 99%